Classification of Crude Oils and its Fractions on the Basis of Paraffinic, Naphthenic and Aromatics - H Al-Dahhan, Wedad; MA Mahmood, Shaymaa (Al-Nahrain Journal of Science, 2019)
The ratios of crude oils hydrocarbons vary according to its origin. Two types of crude oil (A&B) were selected from Dura refinery which was extracted from Basra oil fields. These samples were tested according to physical properties: density, Specific gravity, API gravity, Pour Point, Kw factor and Correlation Index. Results show that crude oil (A) heavier than (B) due to higher density; pour point and lowers (API). Crude oil (A) shows it has more aromatic compounds than the crude oil (B) according to its higher (Kw) and lower (CI) values or (B) contain more paraffinic compounds than (A) for the same reasons. Atmospheric distillation process was done according to ASTM 2892 method for the two selected crude oils. Fractions obtains were tested according to physical properties: density, Aniline Point, API gravity, Kw factor and Correlation Index. The nature of the ingredients for petroleum fractions derived from distillation of the crude oil samples can be classified on the basis of the Paraffinic, naphthenic or aromatic content, depending on the results obtained from distillation which confirm the findings stated above for crude oil. Fourier Transform Infrared Analysis was carried out for crude oils atmospheric fractions to identify the components in terms of being paraffinic, naphthenic or aromatics. Results refers to the same ingredients for crude oil B for the paraffinic and naphthenic components as in crude oil A  but the main difference here is the disappearance of the bands for aromatics C-H stretching occur above 3000 cm-1 for crude oil B which refers that this crude has less aromatic compounds than crude oil A. These results have been confirmed through ultraviolet tests.